2010
DOI: 10.1111/j.1365-2702.2009.03009.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care issues for dysphagia: modifications involving oral fluids

Abstract: The patient's nursing staff typically oversees nutritional care plans that may include modifications to oral fluids to enable their patients to safely drink by mouth. Additional consideration should be given to training procedures and possible noncompliance with preparation guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 28 publications
2
39
0
5
Order By: Relevance
“…These symptoms may be attributed to a reduction in fluid intake, as four of the participants reported drinking less fluid during the thickened liquid period. These findings coincide with prior reports of a decrease in fluid intake among dysphagic patients placed on a thickened liquid diet [8][9][10]. As previously noted, urine density analyses revealed that six out of seven participants had increased urine density after the thickened liquid protocol (see Table 1).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These symptoms may be attributed to a reduction in fluid intake, as four of the participants reported drinking less fluid during the thickened liquid period. These findings coincide with prior reports of a decrease in fluid intake among dysphagic patients placed on a thickened liquid diet [8][9][10]. As previously noted, urine density analyses revealed that six out of seven participants had increased urine density after the thickened liquid protocol (see Table 1).…”
Section: Discussionsupporting
confidence: 80%
“…Several reports have demonstrated that individuals who are placed on thickened liquid diets fail to meet minimum fluid intake requirements and thus are at risk for dehydration [7][8][9]. Patients often report that they don't like the thickened liquids; they refuse to drink them which mean that they reduce their overall fluid intake [10]. Other possible factors to the reduction in fluid intake include the beverage preferences of the patient and incorrect preparation of thickened liquids [1,7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Many patients with dysphagia are prescribed thickened liquids by Doctors of Medicine (MDs), dieticians, registered nurses (RNs), SLPs, and other professionals as a form of compensatory treatment; however, there is variability and a lack of standardization of the preparation of thickened liquids [1][2][3]. A recent study performed by Payne et al shows a statistically significant discrepancy between the thickened liquids prepared by hospital SLPs when compared to thickened liquids prepared in the laboratory, while both groups followed the same instructions [10].…”
Section: Int J Adv Res 5(8) 1197-1216mentioning
confidence: 99%
“…Por otro lado, la prevalencia de las alteraciones de la deglución en pacientes con enfermedades neurológicas y asociadas al envejecimiento es extraordinariamente elevada, extensamente estudiada y, sin embargo, muy poco conocida e infradiagnosticada por el personal sanitario (12,13,19). En las enfermedades neurodegenerativas, las cifras de prevalencia de disfagia orofaríngea son muy altas (19).…”
Section: Algunos Datos Epidemiológicosunclassified
“…En todos los casos se debe individualizar la textura, ya que el uso de dietas modificadas sin individualizar conlleva una clara disminución de la ingesta calórica y proteica (12,15,33,34).…”
Section: Figuraunclassified